Combining field performance with controlled environment plant imaging to identify the genetic control of growth and transpiration underlying yield response to water-deficit stress in wheat - Parent, Boris (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.